Prevalence of multimorbidity and associated factors in the Brazilian working population - de Souza, Ana Clara Dantas (Rev Bras Med Trab, 2021)
INTRODUCTION: According to the World Health Organization (2018), recent changes in the epidemiological profile of working populations point to an increase in non-communicable chronic illnesses and a decrease in communicable chronic illnesses. OBJECTIVES: To estimate the prevalence of multimorbidity in the Brazilian working population (≥18 years) and identify associated factors based on data from the 2013 national health survey (Pesquisa Nacional de Saúde). METHODS: This was a cross sectional study based on data from the 2013 national health survey, which included n = 47,629 people aged 18 years or older. As part of the survey, participants were asked whether they had ever been diagnosed with any of several chronic diseases. The prevalence of multimorbidity in this population and its association with socioeconomic, lifestyle and occupational characteristics were examined. Bivariate analyses were used to calculate prevalence ratios and 95% confidence intervals. Multivariate analyses were conducted using Poisson regression and Wald’s tests to estimate the coefficients of significant variables. RESULTS: The prevalence of multimorbidity was 19.98% (95% confidence interval: 19.29%-20.70%). Higher rates of multimorbidity were associated with female gender, age 60 years or older, living with a spouse, past history of smoking, low education levels (illiterate/primary), living in urban areas, having medical or dental insurance and a history of work accidents. CONCLUSIONS: The prevalence of multimorbidity in the Brazilian population is low. When present, multimorbidity is associated with specific occupational, socioeconomic and lifestyle characteristics.